Protein extraction yield, lipid composition, and emulsifying properties of aqueous extracts of Rhynchophorus phoenicis larvae extracted at pH 3.0 to 10.0. - Aymar Rodrigue Fogang Mba; Elisabeth David-Briand; Michèle Viau; Alain Riaublanc; Germain Kansci; Claude Genot (Future Foods, 2021)
Aqueous extracts of Rhynchophorus phoenicis larvae were prepared at pHs 3.0 to 10.0 to screen their macronutrient composition, emulsifying properties and identify the best conditions to extract a functional protein ingredient. The results showed that the aqueous extracts contained both proteins (0.85 – 4.62 mg/mL), characterized by a large range of molecular weights, and lipids (0.28 to 1.54 mg/mL). The lipids were composed mainly of triacylglycerols (0.21 to 0.95 mg/mL) and free fatty acids (FFA, 0.06 to 0.62 mg/mL) with the highest FFA levels at alkaline pHs; they contained 4.1 to 8.8 g polyunsaturated fatty acids per 100 g total fatty acids. The highest protein extraction yield (54%) of the insect proteins occurred at pH 9.0–10.0. Whatever the extracting pH, the aqueous extracts were able to stabilize oil-in-water emulsions. The emulsions prepared with the pH 9.0 and 10.0 aqueous extracts had however the lowest mean droplet size (d4.3 < 2 µm), and showed no creaming after storage at 4 °C for one weak, indicating that stable emulsions can be prepared at these pHs. Alkaline conditions of extraction will thus be suitable to prepare protein concentrate/isolate of R. phoenicis larvae and test their aptitude to be used to formulate new food products.